L'objet des droits constitutionnels à l'égalité - Proulx, Daniel (Les Cahiers de droit, 1988)
This article is exclusively devoted to enquiring into the purpose of equality rights guaranteed by sections 15 and 28 of the Canadian Charter of Rights and Freedoms. By first retracing the concept of equality from both a legal and philosophical perspective, the author comes to the conclusion that the juxtaposition of values of human dignity and social justice has brought on the most powerful change in the concept of equality. By invoking these two values in unison, authoritative writings, legislators and the courts have on the one hand, come to recognize the insufficiency of formal legal equality and thereby integrate the principle of substantial equality and have, on the other, conceived equality not merely with regard to individuals alone, but also by taking into account groups that society tends to neglect or dominate due to the existence of tenacious prejudices. The author then specifically examines the Canadian legal and socioeconomic context in search of the purpose of equality rights enshrined in the Charter of rights and shows that the addition of section 28 and the enumeration of grounds of discrimination to equality rights in s.s. 15(1) has as its purpose to provide additional protection to women and members of certain underprivileged groups. This special protection is indicative, in the author's view, of a clear constitutional choice in favour of a substantial conception of equality taking into account the collective dimension of discrimination.